Optically anisotropic and photoconducting Langmuir-Blodgett films of neat poly(3-hexylthiophene) - Olivati, C. A. [UNESP]; Goncalves, V. C.; Balogh, D. T. (Elsevier B.V. Sa, 2012)
Among the several types of conjugated polymers used in recent investigations, polythiophene and its derivatives have attracted considerable attention over the past 20 years due to their high mobility and other remarkable solid-state properties. They have potential applications in many fields, such as microelectronic devices, catalysts, organic field-effect transistors, chemical sensors and biosensors. There are two critical parameters that determine the polymer-based device performance: chemical structure and nanostructure of the conjugated polymer in solid state. Langmuir-Blodgett (LB) films may be an interesting alternative for producing the films used in the devices since they can be obtained with high degree of thickness control, low number of defects, and some degree of organization at the molecular scale. However, most of the polythiophene derivatives have poor film forming properties by LB method and need the use of film form aiding materials. In this work, we report on the fabrication and characterization of Langmuir and Langmuir-Blodgett films of neat poly(3-hexylthiophene). Although the LB technique is not suitable to obtain LB films with a great number of layers, good quality films, with thicknesses suitable for fabrication of opto-eletronic devices could be easily built by using the proper deposition conditions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Langmuir-Blodgett films; Polythiophenes; Photoconductivity